Effect of Component Distribution and Nanoporosity in CuPt Nanotubes on Electrocatalysis of the Oxygen Reduction Reaction. Issue 3 (11th December 2014) - Guo, Huizhang; Liu, Xiang; Bai, Chengdong; Chen, Yuanzhi; Wang, Laisen; Zheng, Mingsen; Dong, Quanfeng; Peng, Dong‐Liang
Abstract Pt‐based bimetallic electrocatalysts hold great potential in the oxygen reduction reaction (ORR) in current fuel‐cell prototypes. However, they also face challenges from drastic dealloying of less‐noble metals and coalescence of small nanoparticles. Porous and structure‐ordered nanotubes may hold the potential to improve the stability of bimetallic electrocatalysts. Herein, we report a method to prepare CuPt nanotubes and porous Cu3Pt intermetallic nanorods through a controlled galvanic replacement reaction and heat treatment process. The effect of the geometric features and compositional segregation on the electrocatalysis of the ORR was clarified. The outstanding performance of the Cu3Pt/C‐700 catalyst in the ORR relative to that of CuPt/C‐RT was mainly attributed to the nanoporosity of the catalyst, whereas the enhanced specific activity on CuPt/C‐RT after potential cycling was attributed to the interaction between the CuPt alloyed core and the Pt shell in the tube wall.